GAMBARAN JUMLAH LIMFOSIT PADA PENDERITA HIV YANG MENJALANI TERAPI ARV DI WILAYAH PUSKESMAS MALAWEI KOTA SORONG - Andirwana, Andirwana; Hukom, Evi Hudriyah; Tupanwael, Fenti A; Nurfatimah, Lia; Amir, Nurhidayah; Junaiddin, Junaiddin (Yayasan Healing and Healthcare Education, 2025)
Human Immunodeficiency Virus (HIV) is a virus that attacks T lymphocyte cells and weakens the human immune system. The objective of this study was to describe the lymphocyte count in HIV patients undergoing Antiretroviral Therapy (ART). This research is a descriptive quantitative study with data collection techniques involving Thin Blood Smear examinations. The study was conducted at the Maklawei Health Center Laboratory and the TLM Laboratory of STIKES Papua using a cross-sectional design based on microscopic methods, involving 30 respondents out of a population of 78, selected using random sampling. The respondents were HIV patients actively undergoing ART at the Malawei Health Center in Sorong City. The results showed that among the 30 HIV respondents actively undergoing ART in the working area of the Malawei Health Center, Sorong City, 83.3% (25 respondents) had lymphocyte counts within the normal range (> 20%-40%), while 16.7% (5 respondents) had lymphocyte counts below the normal range (< 20%). In conclusion, this study illustrates that 9 males and 16 females had normal lymphocyte counts, while 1 male and 4 females had lymphocyte counts below normal. This indicates that ART successfully helps maintain the immune system. The government and related parties must ensure the availability of ART to improve health and reduce the risk of infections in HIV patients.